2020
DOI: 10.25095/mufad.673679
|View full text |Cite
|
Sign up to set email alerts
|

Çalışma Sermayesi Yönetiminin Kârlılığa Etkisi: Borsa İstanbul 50 Endeksi Örneği

Abstract: Bu çalışma işletme sermayesi bileşenlerinin kârlılık üzerindeki etkilerini incelemektedir. Bu amaçla Borsa İstanbul (BİST) 50 endeksinde işlem gören ve mali kuruluş olmayan 33 işletmenin 2012-2016 yılları arasındaki finansal ve finansal olmayan verileri çoklu regresyon ve korelasyon yöntemleri ile analiz edilmiştir. Çalışma sonuçlarına göre ilgili şirketlerin nakit dönüş süreleri ile hem aktif kârlılığı hem de faaliyet kârı arasında anlamlı ilişki belirlenememiştir. Buna karşın aktif kârlılığı ile şirket yaşı … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In addition, this finding is capable of explaining the diminishing impact of the costs of holding excessive current assets on profitability. In line with the literature (Akbulut, 2011;Çakır and Küçükkaplan, 2012;Saldanlı, 2012;Toraman and Sönmez, 2015;Keskin and Gökalp, 2016;Güdelci, 2016;Eskin and Güvemli, 2020;Yıldız and Deniz, 2020;Çanakçıoğlu and Ersan, 2020;Akbulut, 2011;Çakır and Küçükkaplan, 2012;Saldanlı, 2012;Toraman and Sönmez, 2015;Yunos et al, 2015;Keskin and Gökalp , 2016;Güdelci, 2016), the cash conversion cycle was found to have no influence on the return on assets.…”
Section: Conclusion and Recommendationssupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, this finding is capable of explaining the diminishing impact of the costs of holding excessive current assets on profitability. In line with the literature (Akbulut, 2011;Çakır and Küçükkaplan, 2012;Saldanlı, 2012;Toraman and Sönmez, 2015;Keskin and Gökalp, 2016;Güdelci, 2016;Eskin and Güvemli, 2020;Yıldız and Deniz, 2020;Çanakçıoğlu and Ersan, 2020;Akbulut, 2011;Çakır and Küçükkaplan, 2012;Saldanlı, 2012;Toraman and Sönmez, 2015;Yunos et al, 2015;Keskin and Gökalp , 2016;Güdelci, 2016), the cash conversion cycle was found to have no influence on the return on assets.…”
Section: Conclusion and Recommendationssupporting
confidence: 86%
“…The results of studies that use the CCC to investigate the relationship between working capital efficiency and profitability have been inconsistent. While some studies (Gill, Biger and Mathur, 2010;Sharma and Kumar, 2011;Mansoori and Muhammad, 2012;Akoto et al, 2013;Aksoy, 2013;Çakır, 2013;Ata and Buğan, 2016;Akyüz et al, 2019;Çerçel and Sökmen, 2019;Akomeah and Frimpong, 2019;Eskin and Güvemli, 2020) have reached the conclusion that the impact of efficiency on profitability is positive, others (Öz and Güngör, 2007;Şamiloğlu and Demirgüneş ,2008;Ata, Gür and Yakut, 2008;Şen and Oruç, 2009;Uyar, 2009;Karaduman, Akbaş, Özsözgün et al, 2010;Mathuva, 2010;Dong and Su, 2010;Charitou et al, 2010;Mohamad and Saad, 2010;Coşkun and Kök, 2011;Abuzayed, 2012;Napompech, 2012;Dursun and Ayrıçay, 2012;Aygün, 2012;Vural, Sökmen and Çetenak, 2012;Makori and Jagongo, 2013;Demireli, Başcı and Karaca, 2014;Kendirli and Konak, 2014;Ukaegbu, 2014;Yazdanfar and Öhmen, 2014;Tu and Nguyen, 2014;Aytürk and Yanık, 2015;Fettahoğlu and Mohamud, 2016;Helhel and Karasakal, 2017;…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Baykut and Kula (2018), the volatility structure of the BIST 50 index was examined over the daily closing values for the 2007-2016 period. In a study conducted by Eskin and Güvemli (2020) to examine the effects of working capital components on profitability, the financial and non-financial data of 33 businesses that are traded in the Borsa Istanbul (BIST) 50 index and that are not financial institutions between 2012 and 2016, using multiple regression and correlation methods. analyzed with As a result of the study by Wang and Kong (2021), it was found that economic policy uncertainty has a negative impact on the energy stock market in China, and the energy stock market is also positively affected by the country's overall stock market.…”
Section: Consumer Confidence Indexmentioning
confidence: 99%